Knockout of sodium channel Nax delays re‐epithelializathion of splinted murine excisional wounds. Issue 2 (30th December 2020) - Hou, Chun; Dolivo, David; Rodrigues, Adrian; Li, Yingxing; Leung, Kai; Galiano, Robert; Hong, Seok Jong; Mustoe, Thomas
Abstract: Mammalian wound healing is a carefully orchestrated process in which many cellular and molecular effectors respond in concert to perturbed tissue homeostasis in order to close the wound and re‐establish the skin barrier. The roles of many of these molecular effectors, however, are not entirely understood. Our lab previously demonstrated that the atypical sodium channel Nax (encoded by Scn7a ) responds to wound‐induced epidermal dehydration, resulting in molecular cascades that drive pro‐inflammatory signaling. Acute inhibition of Nax was sufficient to attenuate dermatopathological symptoms in models of hypertrophic scar and dermatitis. To date, however, the role of Nax in excisional wound healing has not been demonstrated. Here we report development of a knockout mouse that lacks expression of functional Nax, and we demonstrate that lack of functional Nax results in deficient wound healing in a murine splinted excisional wound healing model. This deficiency in wound healing was reflected in impaired re‐epithelialization and decreased keratinocyte proliferation, a finding which was further supported by decreased proliferation upon Nax knockdown in HaCaT cells in vitro. Defective wound healing was observed alongside increased expression of inflammatory genes in the wound epidermis of Nax −/− mice, suggesting that mice lacking functional Nax retain the ability to undergo skin inflammation. Our observations here motivate further investigation into the roles of Nax in wound healing and other skin processes.